Implementasi Program Lombok Timur Berkembang (Berantas Rentenir Melalui Kredit Tanpa Bunga) Pada Umkm Di Kecamatan Selong - Juani, Muhamad; Utomo, Danang Prio; Ali, Muhamad (Universitas Hamzanwadi, 2023)
Implementation is the process of putting a plan, decision, or policy into action. Implementation also includes a number of actions, such as planning, preparing resources, organizing leading, and carrying out an action or decision. This study aims to determine how the implementation of the Lotim Berkembang program in improving the development of MSMEs in Selong sub-district and what are the inhibiting factors in the implementation of the Lotim berkembang program. The research used in this study is descriptive research with a qualitative approach. The data obtained is then analyzed by reducing the data, presenting the data and drawing conclusions. This research is based on the theory of Edwar III, which uses 4 factors as a research reference, namely resources, communication, bureaucratic structures, and attitudes. The results of the Lotim Berkembang Program Implementation Research on MSMEs in Selong District show that the implementation of the Lotim Berkembang program is quite good but not yet fully successful. The recipients of the Lotim Berkembang program feel very helpful in developing their business. The obstacles in the implementation of this program are more likely to be from people who are difficult to gather, and communion.